Local movements and habitat use of Tundra or Whistling Swans Cygnus columbianus in Kobuk-Selawik Lowlands of northwest Alaska - Spindler, Michael A; Hall, Kent F (Wildfowl, 1991)
A radio telemetry study of Tundra or Whistling Swans in the Kobuk-Selawik Lowlands of northwest Alaska 1984-89 showed that late summer home range size differed according to breeding status. Family groups moved less than flocked non-breeders, with ranges averaging 139 ha and 1331 ha, respectively. Late summer movements of family groups usually centered on one to three wetlands, although some family groups and non-breeding pairs ranged over a dozen wetlands. Flocked non-breeders exhibited widespread late summer movements, departing to staging areas soon after regaining flight. Tundra Swans selected late summer home ranges that contained more water and wetlands, 41-47% by area, than available habitat which had only 19% water and wetlands. All flocked non-breeders made a staging movements whereas 71% of territorial non-breeding pairs and 68% of family groups made such staging movements. Flocked non-breeders moved to staging areas earliest, departed latest, and staged for the longest duration, while family groups were the last to initiate staging and had the shortest staging duration. Family groups and territorial non-breeders that did not stage averaged earlier departure on migration than other swans. Family groups and flocked non-breeders moved an average of 30 and 49 km, respectively, from late summer home ranges to autumn staging areas. Brackish shorelines of river deltas in the study area provided an abundance of Potamogeton tubers and remained clear of ice later than other wetlands. Delta tidelands are of major importance to the regional Tundra Swan population because they likely provide food critical to autumn migration.